Pulmonary Tuberculosis in Dermatological Patients on High-Dose, Long-Term Steroid Therapy - Kalsoom Aslam, Farooq Azam Khan, Hafsa Usman, Kausar Masoom, Syed Ehsanullah, Abdul Qayum Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tuberculosis is a dangerous infection that can affect the vital organs of the body. Steroid is the cornerstone of immunosuppressive treatment disorders in dermatology. Objective: The aim of the study was to find out the frequency of Pulmonary tuberculosis in dermatological patients on high-dose, long-term steroid therapy. Methodology: The current study was conducted at the Dermatology department, Kuwait teaching hospital Peshawar from January 2022 to November 2022 after taking approval from the ethical committee of the institute. Individuals who presented to the dermatology department, met the inclusion criteria (patients of either sex, in the adult (≥12 years) age range, and needed high dosage, continuous systemic steroid treatment for their skin condition) were enrolled. To assess for pulmonary tuberculosis, patients were checked on every three months, six weeks, and six months following treatment. Sputum smears for acid-fast bacilli (AFB) were performed for three days straight at each appointment. In cases where more than one sputum smears tested positive for AFB, no further testing was done. An X-ray of the chest was taken to look for any anomalies that would be compatible with active pulmonary TB if just one sputum smear tested positive for AFB. The data was imported into the SPSS (Statistical Package for the Social Sciences) version 19 computer software application and examined as necessary. The quantitative variables were shown using the mean, median, and standard deviation. To determine the P value, the McNamara test was used. Results: A total 54 individuals with skin diseases needing high-dose systemic steroid treatment over an extended period of time participated in this study. Out of which 26(48.1%) were male and 28 (51.85%) were females. The patients’ ages ranged from 15 to 75. After a duration of three months, 4 individuals (7.4%) out of 54 receiving high dosage long-term systemic steroid treatment developed pulmonary TB (P=0.0001). Conclusion: This study evaluated 7.4% pulmonary tuberculosis among individuals receiving large doses of systemic steroid treatment over an extended period of time. Keywords: Pulmonary tuberculosis; Dermatological patients; High-dose, Steroid therapy